REACH-OUT OF ECCE DIPLOMA PROGRAMME - CHANDRA, REETU (THE PRIMARY TEACHER, 2012)
Early Childhood Care and Education (ECCE) is an integral part of school education, which has strong bearing specially upon primary education. It is also an important component for achieving universal enrolment and retention in primary schools. Therefore, proper linkage must be ensured between pre-primary and primary schools. It can only be done by providing necessary maturational and experiential readiness to the children at pre-primary level for meeting the demands of primary education curriculum. This readiness depends on child’s early care and education, which includes health care, nutritional support and psychosocial stimulation. Ensuring availability of qualified and trained teachers in ECCE/ pre-primary centres would be an essential condition for achieving.